Pendidikan Dan Pengetahuan Ibu Hamil Trimester III Dengan Sikap Terhadap Inisiasi Menyusui Dini - Theresia Limbong; Rika Handayani; Asridawati Akib (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Breastfeeding can protect infants and toddlers; therefore, it is advisable to breastfeed as soon as possible after the baby is born. Early contact between mother and baby is a sensitive period in which an earlier delay in contact between the baby and the mother will interfere with the child's further development. Various reasons are put forward by mothers who do not exclusively breastfeed their babies, including mothers who feel less milk production, difficulty in sucking babies, working mothers, the desire to be modern, and the influence of advertising/promotion of breast milk substitutes. This study aimed to determine the relationship between education and knowledge on changes in attitudes of III trimester pregnant women about Early Breastfeeding Initiation. Analytical research with a Cross-Sectional Study approach with a sample of 31 people. Data processing with SPSS with Chi-Square test. The study's results did not show a relationship between education and knowledge in the attitude of III trimester pregnant women towards Early Initiation of Breastfeeding. Every expectant mother is unique, and the approach to teaching and understanding can be tailored to their needs and preferences. Supporting expectant mothers with accurate information, emotional support, and appropriate resources can help improve their attitudes toward early breastfeeding initiation and prepare them for a positive breastfeeding experience.